Structure and magnetic properties of [Co/Pd] multilayer nano antidots thin films with perpendicular magnetic anisotropy - Giap, Van Cuong; Chu, Van Thanh; Do, Khanh Tung; Nguyen, Thanh Huong; Do, Hung Manh; Tran, Dang Thanh; Nguyen Thi, Ngoc Anh (Journal of Military Science and Technology, 2022)
The [Co/Pd] multilayer nano antidots thin films sputtered on the Al2O3 and TiO2 nanoporous templates with pore sizes of 30 nm and 50 nm were fabricated by DC magnetron sputtering. The impact of film morphology on the structural and magnetic properties in the deloveloped films are thoroughly investigated. The results show that, similar to the [Co/Pd] multilayer flat thin film, the multilayer antidot films also show large perpendicular magnetic anisotropy at room temperature. However, the coercivity of HC in the multilayer antidot films is significantly enhanced compared with that of the flat film, the highest HC of 2220 Oe was achieved for the TiO2-[Co/Pd] multilayer antidot film, which is respectively 1.28 and 3.15 times higher than that of the Al2O3-[Co/Pd] multilayer antidot film and the SiO2-[Co/Pd] flat thin film, due to the formation of magnetically soft regions near the pore edges. It can be said that the magnetic properties in the antidots multilayer thin films can be completely modulated by adjusting the structural parameters of the nanoporous template such as pore size and surface roughness.